2023
DOI: 10.1002/cey2.349
|View full text |Cite
|
Sign up to set email alerts
|

Binary molten salt in situ synthesis of sandwich‐structure hybrids of hollow β‐Mo2C nanotubes and N‐doped carbon nanosheets for hydrogen evolution reaction

Abstract: Focused exploration of earth‐abundant and cost‐efficient non‐noble metal electrocatalysts with superior hydrogen evolution reaction (HER) performance is very important for large‐scale and efficient electrolysis of water. Herein, a sandwich composite structure (designed as MS‐Mo2C@NCNS) of β‐Mo2C hollow nanotubes (HNT) and N‐doped carbon nanosheets (NCNS) is designed and prepared using a binary NaCl–KCl molten salt (MS) strategy for HER. The temperature‐dominant Kirkendall formation mechanism is tentatively pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…34 The Mo 3d spectra (Fig. 3e) reveal three feature states: Mo 6+ (235.7 eV), Mo 4+ (232.5 eV), and Mo 2+ (228.8 eV), and Mo in the high-valence state may be caused by the surface oxidation of Mo 2 C. 35 However, the existence of the C–N bond and Mo–N bond in the sample indicates that strong interactions between electrons can promote electron transfer. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The Mo 3d spectra (Fig. 3e) reveal three feature states: Mo 6+ (235.7 eV), Mo 4+ (232.5 eV), and Mo 2+ (228.8 eV), and Mo in the high-valence state may be caused by the surface oxidation of Mo 2 C. 35 However, the existence of the C–N bond and Mo–N bond in the sample indicates that strong interactions between electrons can promote electron transfer. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…36 These analyses further indicate that Mo 2 C and C are successful combined and N element is successful doped, resulting in multiple heterointerfaces that can trigger multiple polarization relaxation to promote electromagnetic dissipation ability. 35…”
Section: Resultsmentioning
confidence: 99%
“…A low overpotential of only 98 mV was obtained to reach a current density of 10 mA cm −2 . 89 In recent years, a double carbon target (carbon neutrality and carbon peak) has become the aim of many countries, inspiring numerous scientists to engage in the conversion and utilization of CO 2 into value-added chemicals/materials. Excellent electrical conductivity is another feature of molten salts, which can expand their application scope.…”
Section: Approachmentioning
confidence: 99%
“…1 Hydrogen is recognized as an ideal energy carrier owing to its high energy density and zero carbon emission. 2 Among various hydrogen production methods, electrochemical water splitting is considered to be an environmental friendly and sustainable method to produce high-purity hydrogen. 3,4 Fundamentally, electrochemical water splitting consists of two half-reactions: the hydrogen evolution reaction (HER) on the cathode and oxygen evolution reaction (OER) on the anode.…”
Section: Introductionmentioning
confidence: 99%
“…6 Noble metal (Ir and Ru) based electrocatalysts show a good OER activity; however, the scarcity and high cost seriously restrict their wide application. 7,8 In recent years, researchers have revealed that transition metal-based oxides, 9–11 sulfides, 12,13 phosphides, 14,15 carbides 2,16,17 and alloys 18,19 also show promising catalytic properties for both the HER and OER, which are expected to replace precious metal oxide electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%